On criticality coupled sub-Laplacian systems with Hardy type potentials on Stratified Lie groups - Jinguo Zhang; Shuhai Zhu (Communications in Analysis and Mechanics, 2023)
In this work, our main concern is to study the existence and multiplicity of solutions for the following sub-elliptic system with Hardy type potentials and multiple critical exponents on Carnot group